Creative Content Production Challenge and Engagement Instability Analysis of Bu Erte’s Woven Bags on Tiktok - Laylia Putri Ramadhanie; Restin Meilina (Journal of International Conference Proceedings, 2025)
This research investigates the content strategy of traditional craft MSMEs (Micro, Small, and Medium Enterprises) in response to engagement instability on TikTok. The study's significance lies in its effort to fill the literature gap regarding the impact of algorithmic uncertainty on the creative decisions of micro-entrepreneurs. Its objective is to analyze the meaning and adaptation strategies employed by the owner of "Tas Anyaman Bu Erte" (Bu Erte's Woven Bags) in managing fluctuations in audience involvement. Utilizing a qualitative case study approach, the research findings reveal that a reactive response to engagement instability actually triggers a simplification of content into static formats, which further decreases interaction. The findings indicate that audiences value content that transparently showcases the craftsmanship process more highly than content that merely follows viral trends. The study's implication suggests the necessity of shifting focus toward a hybrid content strategy that balances trend adaptation with product quality education to build sustainable customer trust.